A Handbook on Image Processing and Wireless Communication - Nikhil Ranjan,; Pankaj Dadheech,; Sanwta Ram Dogiwal, (AG Volumes, 2022)
In field of Artificial Intelligence (AI), Artificial Neural Networks (ANNs) have been widely accepted as a cutting-edge computing technology. There is a lot to learn about AI and ANN in this study, which focuses on modern applications of these technologies. Using a combination of Neural Networks (NNs) and fuzzy logic, it hopes to improve the data's capacity to be interpreted. The past two decades, ANNs have been intensively explored and deployed as a major soft-computing technique. Pattern recognition, data analysis, control, and grouping are most common uses of NNs in problem solving. There are several advantages to ANNs, including rapid processing rates and the capacity to learn from examples. Research in this article focuses on the newest applications of NNs and offers an overview of the sector in which NNs are utilized. It explores how NNs play a key role in several fields, such as AI.